Nilai Viral Load dan Cluster of Differentiation 4 (CD-4) pada Pasien Human Immunodeficiency Virus (HIV) sebagai Penanda Infeksi Menular Seksual - Utiya Nur Laili; Endra Yustin Ellistasari; Putri Jati Utami; Larisa Sabrina Rahadiyanti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Human immunodeficiency virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) infection is a major problem in developing countries. Co-infection with sexually transmitted infections (STIs) in HIV patients is a comorbid factor increasing the risk of HIV and STI transmission. CD4 T lymphocyte cell levels and viral load are used for immunologic and virologic success of HIV/AIDS patients. Studies linking CD4 T lymphocyte counts, viral load and STI incidence in HIV/AIDS patients are few and variable. This research aim to evaluate the CD4 and viral load values in HIV/AIDS patients at Dr. Moewardi Hospital with the incidence of STIs. Retrospective study using secondary data from the medical records of the Voluntary Counseling and Testing (VCT) clinic at Dr. Moewardi Hospital for the period January 2022 - December 2024. Sexually transmitted infections diagnosis was based on syndromic approach. Data CD4 of STI patients with HIV/AIDS were recorded for statistical processing using SPSS version 26. Numerical data were tested for normality using the Kolmogorov-Smirnov test (p>0.05). Normally distributed data were subjected to unpaired t-test, non-normally distributed data were subjected to Mann-Whitney test, categorical data were subjected to chi-square test with a significance of p<0.05. CD4 data were then assessed for sensitivity, specificity and cut-off values. Cases of HIV patients with STIs were predominantly male with an average age of 33.94 years. Statistical analysis showed gender (p=<0.001), occupation (p=0.018) age (p<0.001), and ARV duration (p=0.037), while education level (p=0.448) and viral load (p=0.417). CD4 count (p=0.027) had p<0.05, AUC for CD4 was 0.648 with p=0.030, cutoff 459.5, sensitivity 66.7% and specificity 62.5%, OR=3.33 and p=0.013. There is an association between CD4 levels and the incidence of STIs in HIV patients with a sensitivity of 66.7%, specificity of 62.5% and a cutoff value of 459.5, HIV patients with CD4 <459.5 have a risk of STIs by 3.33 times compared to HIV patients who have CD 4 ≥459.5 (OR = 3.33; p = 0.013).